2021
DOI: 10.21203/rs.3.rs-587686/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Testing and Vaccine Hesitancy in Latinx Farm-Working Communities in The Eastern Coachella Valley

Abstract: Background A novel coronavirus, SARS-CoV-2 (known as COVID-19), spread rapidly around the world, affecting all and creating an ongoing global pandemic. In the United States, Latinx, African American, and Indigenous populations across the country have been disproportionately affected by COVID-19 cases and death rates. An examination of the perceptions and beliefs about the spread of the virus, COVID-19 testing, and vaccination amongst racial/ethnic minority groups is needed in order to alleviate the widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…This is reassuring given the legitimate concern that access to vaccination would be limited for this population. Early in the vaccination roll-out, qualitative research among primarily female migrant farmworkers in the USA and migrants with precarious immigration status in the UK showed that misinformation and lack of awareness about entitlements, including access to COVID-19 vaccines, could present substantial barriers to immunisation programmes 45 46. In our study, women were more likely to endorse access than men.…”
Section: Discussionmentioning
confidence: 57%
“…This is reassuring given the legitimate concern that access to vaccination would be limited for this population. Early in the vaccination roll-out, qualitative research among primarily female migrant farmworkers in the USA and migrants with precarious immigration status in the UK showed that misinformation and lack of awareness about entitlements, including access to COVID-19 vaccines, could present substantial barriers to immunisation programmes 45 46. In our study, women were more likely to endorse access than men.…”
Section: Discussionmentioning
confidence: 57%
“… 14 , 15 For immigrant, migrant, and Indigenous Latinx individuals, lack of trust in institutions and misinformation also reduce the likelihood of testing. 16 Reducing testing barriers and overcoming health disparities for Latinx communities require culturally responsive interventions, including not requiring health insurance, physician orders, identification, or fees and offering walk-up service. 15 , 17 Although several programs to reduce barriers to SARS-CoV-2 testing for Latinx communities exist, 14 , 15 , 17 , 18 to our knowledge, this is the first randomized trial to evaluate strategies designed to accelerate SARS-CoV-2 testing among Latinx populations.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is that we assumed discordant vaccination status (e.g., only the susceptible worker had received a vaccination) among the infected and susceptible produce workers modeled. While vaccine hesitancy has been well documented among the food worker population 94,95 , these findings suggest that promoting a single-dose or two-dose vaccine can reduce daily infection risk by roughly 73.0% or 93.0%, respectively. Future work is needed to understand the SARS-CoV-2 vaccination coverage levels within this essential worker community, the findings of which could then be incorporated into the present model to increase the generalizability of our results.…”
Section: Discussionmentioning
confidence: 87%